Development and testing of Malaysian career factors inventory - Md. Yasin, Ina (2014)
The study was conducted to identify how implicit social cognition via Theory of Planned Behaviour with the adoption of Rogoff‟s Three Planes of Analysis was used as mediator for the development of Malaysian Career Factors Inventory (MyCFI). Therefore, the proposed model in this study (Personal, Attitude, Interpersonal, Perceived Behavioural Control, Historical Organisation and Subjective Norms or so called PAIPHOSN Model) is premised on the notion that sociocultural approach may lead to a further understanding of the assumption on cognition as a collaborative process. The development and testing of MyCFI was used to measure career indecision among students at public universities in Malaysia. This study examined the role that implicit processes may play in human thoughts and behaviour and to identify the relationships between implicit social cognition and behavioural intention towards career decision for future orientation. Specifically, the objectives of this research were i) to examine Career Factors Inventory (CFI) for the construction of a local version of CFI called Malaysian Career Factors Inventory (MyCFI); ii) to test and validate MyCFI among students at public universities in Malaysia; iii) to identify what are the domains related to career indecision among students at the public universities in Malaysia; and iv) to identify the association of career indecision with the demographic characteristics of the students at public universities in Malaysia. A total of 2607 students from 12 public universities in Malaysia participated in this research. The data was collected and completed upon the students registering at a career expo in Universiti Putra Malaysia (UPM). The reliability of instrument used was remarkable with alpha value ranging from 0.656 to 0.900 which considered as acceptable since the value is more than 0.65. Besides, this study was supported with the use of statistical analyses namely, level analysis test, t-test, ANOVA, simple regression, Pearson correlations and multiple regression analysis. Based on the development and testing of MyCFI, this study revealed that Career Choice Anxiety, Need for Career Information and Need for Self Knowledge are the implicit social cognition domains that influenced career indecision among students at public universities in Malaysia. At the same time, there is no significant means between the aspects of gender and age towards career indecision. Finally, another remarkable finding was when the student grouped from science based faculties were found to have the highest percentage rate for attendance at the career expo and simultaneously justified them of having greater needs for career guidance.